2009
DOI: 10.1007/s12217-009-9122-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gravity on the Dynamics of Non-Isothermic Ultra-Thin Two-Layer Films

Abstract: The development of instabilities under the joint action of the van der Waals forces and Marangoni stresses in a two-layer film in the presence of an inclined temperature gradient, is investigated. The problem is solved by means of a linear stability theory and nonlinear simulations. The influence of the gravity on the instabilities of non-isothermic two-layer films is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Note that (i) we include gravity terms in the pressures, since it has been shown that these terms may be important in a certain range of parameters [28,34], and (ii) we do not include the electronic component in the disjoining pressures [60], since for a single layer as well as for a bilayer system the inclusion of the electronic component does not result in the noticable improvement in matching of the theoretical predictions to the experiment, such as, for instance, the prediction of the critical film thickness at which the transition from bicontinuous structures to holes takes place [13,61]. The surface tension gradients, ∂ x σ 1,2 in Eqs.…”
Section: Evolution Equations For the Bilayermentioning
confidence: 99%
See 2 more Smart Citations
“…Note that (i) we include gravity terms in the pressures, since it has been shown that these terms may be important in a certain range of parameters [28,34], and (ii) we do not include the electronic component in the disjoining pressures [60], since for a single layer as well as for a bilayer system the inclusion of the electronic component does not result in the noticable improvement in matching of the theoretical predictions to the experiment, such as, for instance, the prediction of the critical film thickness at which the transition from bicontinuous structures to holes takes place [13,61]. The surface tension gradients, ∂ x σ 1,2 in Eqs.…”
Section: Evolution Equations For the Bilayermentioning
confidence: 99%
“…This applied modeling paper is motivated by the recent experiments on dewetting of non-reactive, immiscible metallic bilayers [16], and the need to better understand the physical mechanisms leading to spatial ordering of particles and the morphological pathways towards the final particle morphologies. The experimental [17][18][19][20][21][22][23][24] and theoretical [25][26][27][28][29][30][31][32][33][34] studies of the instabilities and dynamics of bilayer thin films so far have been largely limited to aqueous and polymer systems under isothermal conditions. Non-isothermal dewetting even in such more conventional systems has not been fully investigated theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown by Nepomnyashchy and Simanovskii (2009) in the framework of a linear stability theory that parameter g 2 is a major stabilizing factor, while the influence of the density stratification parameter g 1 − g 2 is much weaker. Therefore, we perform simulations with different values of g 2 when keeping g 1 = 0.02.…”
Section: Constant Gravitymentioning
confidence: 99%
“…They resulted from strong discontinuity relations for generalized fluid-fluid motions as the relations of mass, impulse and energy balance by transition through the interface. The influence of the gravity on the instabilities of non-isothermal two-layer films and the development of instabilities under the action of Marangoni stresses and van der Waals forces were investigated in (Nepomnyashchy and Simanovskii 2009).…”
Section: Introductionmentioning
confidence: 99%